Clinical application of dendrimer in cancer and COVID-19 therapy: a review - Devita, Ninda; Nurfadilah; Siti Khadijah; Ulil Albab Habibah (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Dendrimers are nanoparticles with unique characteristics. These characteristics allow these nanoparticles to be widely applied in medicine. It can be used as a therapy for various types of cancer. The dendrimers can also been use an alternative to accelerating the diagnosis and therapy of COVID-19. This review aimed to delve deeper into the myriad clinical applications of dendrimers in the treatment of various cancers and its potential use for the treatment or diagnosis of COVID-19. The databases used for this review were Google Scholar and Science Direct. The inclusion criteria for this review are articles published in 2018-2023. Articles other than the original articles and reviews we excluded from the study. Anticancer formulated in dendrimers have a better ability to eradicate cancer cells in the treatment of breast, colon, lung, prostate, skin, ovarian, and liver cancers compared to ordinary anticancer agents. Dendrimer in vivo, in vitro and phase II clinical trials can be used to deliver miRNA therapy or symptomatic drugs in COVID-19 patients and as vaccine delivery agents. The quality of molecular diagnosis of COVID-19 can also be improved with these nanoparticles. The use of dendrimers can improve the quality of management of cancer and COVID-19 patients.